Do International Organizations have a Territory? Some General Reflections and the Special Case of the European Union - Boisson de Chazournes, Laurence; Kuijper, Pieter (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
The article explores the largely overlooked question of whether international organizations have a defined territory, noting that founding treaties of bodies such as the World Trade Organization (WTO), the International Monetary Fund (IMF), or the World Bank generally remain silent on this issue. Many agreements establishing free trade areas in Africa, Asia, or the Americas even omit territorial definitions, with notable exceptions like the US–Mexico–Canada Agreement. The European Union (EU), however, stands apart, as its treaties expressly define territorial scope (Articles 52 Treaty on European Union and Article 355 of the Treaty on the Functioning of the European Union), a reflection of its colonial legacy and evolving institutional practice. The analysis develops in two stages: first, it explains how EU law has created a distinct legal notion of “EU territory” through treaty provisions, case law, and institutional collaboration between EU and national authorities; second, it considers how courts and institutions have consolidated this concept in practice, including in areas such as border management, competition law, and extraterritorial application of EU rules. The article concludes with a “layered” approach, where the EU’s legal territory overlays the physical territories of Member States while remaining subject to international law. This layered conception demonstrates how the EU, unlike most international organizations, has gradually developed its own recognizable territorial dimension.